2011
DOI: 10.1111/j.1365-2834.2011.01272.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors contributing to contemporary nursing shortage in Macao

Abstract: There is an urgent need to improve the management of nurses' workloads and to communicate better with frontline nursing staff on issues such as payment and employee benefits, the number of staff on duty and continuing nursing education.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…In agreement with the findings of this study, in the study of Leong, economic issues were part of the dissatisfaction expressed by the interviewees. Concerns were raised about both salary and employee benefits, and one can conclude that policies in these areas are met with some dissatisfaction [24]. Therefore, imagination of imminent future demotivates nursing students.…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with the findings of this study, in the study of Leong, economic issues were part of the dissatisfaction expressed by the interviewees. Concerns were raised about both salary and employee benefits, and one can conclude that policies in these areas are met with some dissatisfaction [24]. Therefore, imagination of imminent future demotivates nursing students.…”
Section: Discussionmentioning
confidence: 99%
“…, Hughes , Gallagher , Penz et al . , Schweitzer & Krassa , Leong ). Increased workloads including the type and quantity of nursing work, patient to nurse ratios and patient acuity are documented as barriers to CPD (Barriball , Penz et al .…”
Section: Introductionmentioning
confidence: 99%
“…Two qualitative studies identified a lack of available nurses created an additional difficulty of finding replacement staff for those attending CPD, causing further staffing level concerns (Berridge et al . , Leong ). This has implications for skill mix (Joyce & Cowman ), without adequate backfill nurses in practice face an increased workload and responsibility for patient care and safety (King & McInerney ).…”
Section: Introductionmentioning
confidence: 99%
“…Nurses can give professional care and health education to older people to enhance their quality of life (Yi, Chen, Jia, & Lu, ). However, health and aged care services are unable to meet the increasing demand (Baumann, ; Leong, ; Yun, Jie, & Anli, ). Therefore, identifying and addressing self‐care deficits can support older people to remain at home with minimum support.…”
Section: Introductionmentioning
confidence: 99%